2021
DOI: 10.1155/2021/3157867
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a Novel Therapeutic Approach for Lymphoma

Abstract: Lymphoma is a name for malignant diseases of the lymphatic system including Hodgkin’s lymphoma and non-Hodgkin’s lymphoma. Although several approaches are used for the treatment of these diseases, some of them are not successful and have serious adverse effects. Therefore, other effective treatment methods might be interesting. Studies have indicated that plant ingredients play a key role in treating several diseases. Some plants have already shown a potential therapeutic effect on many malignant diseases. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 145 publications
(135 reference statements)
0
14
0
Order By: Relevance
“…Quercetin is a natural bioflavonoid compound extracted from Hippophae rhamnoides, and it can significantly inhibit the progression of multiple cancers. For example, Mohammed et al (2021) found that quercetin induced the apoptosis and inhibited the invasion of breast cancer cells; Soofiyani et al (2021) indicated that quercetin acted as a novel agent for the treatment of lymphoma. Quercetin has also been shown to be able to inhibit the growth of CRC cells ( Qi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is a natural bioflavonoid compound extracted from Hippophae rhamnoides, and it can significantly inhibit the progression of multiple cancers. For example, Mohammed et al (2021) found that quercetin induced the apoptosis and inhibited the invasion of breast cancer cells; Soofiyani et al (2021) indicated that quercetin acted as a novel agent for the treatment of lymphoma. Quercetin has also been shown to be able to inhibit the growth of CRC cells ( Qi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The specific effect of quercetin on tumor cells without any impact on normal or nontransformed cells has compelled many researchers to explore its potential use as an adjuvant in suppressing proliferation, metastasis, epithelial–mesenchymal transition (EMT), and oxidative stress [ 31 33 ]. Having more potent antitumor activity, fewer side effects, and cost-effectiveness, natural products are promising candidates for pharmaceutical development as anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…luteolin, an active ingredient extracted from Codonopsis Radix and Pseudostellariae Radix, has been tested to inhibit the proliferation of classical Hodgkin’s lymphoma cells via caspase activation ( Gharbaran et al, 2020 ). Quercetin, an active ingredient of Astragali Radix and Glycyrrhizae Radix et Rhizoma, has been detected to inhibit cancer cell growth by modulating AKT and NF-κB pathways in lymphoma models ( Soofiyani et al, 2021 ). The experimental results also displayed the prospect of Qi-invigorating herbs in DLBCL treatment.…”
Section: Discussionmentioning
confidence: 99%